“We Have a Right to This Tradition”: The Cosmopolitan Writer and Liberal Right (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
The vast critical bibliography that has dealt with “The Argentine Writer and Tradition” overlooked a crucial detail for the conceptualization of Borges’ cosmopolitanism: the essay characterizes the relationship of the marginal/interstitial writer to Western/universal culture in terms of a cosmopolitan right that must be read in relation to the liberal philosophical and political tradition that extends from John Stuart Mill’s “On Liberty” (1859) to Isaiah Berlin’s “Two Concepts of Liberty” (1958). Based on this new interpretation and historicization of Borges’ cosmopolitanism, this article presents a re-reading of “The Argentine Writer and Tradition,” but also of the relationship between literature and justice and of the rough edges that connect and pull apart the notion of right at stake in Borges’ essay and the civil rights that Perón’s government sanctioned and curtailed.